DEVELOPMENT OF STATE FINANCIAL CONTROL IN THE TAX SYSTEM OF UKRAINE IN THE CONDITIONS OF INNOVATIVE TRANSFORMATIONS - GAVKALOVA, Natallia; TABATSKYI, Maksym; SHVABII, Kostiantyn (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article defines the essence, functions, and types of state financial control. State financial control is an integral part of the management of economic objects and processes, which consists of observing the object to verify the compliance of the object of observation with the desired and necessary state. The task of state financial control is defined. The main functions of state financial control are highlighted. The main problems and the need to improve the system of state financial control in Ukraine were considered, and the State Control and Audit Service's activity in financial control was investigated. The theoretical principles of determining the essence, role, and place of state financial control in the system of financial activity of the state have been studied as an organic component of the market economy - an essential factor in achieving a balance between market relations and state regulation in order to achieve a strategic effect based on the consequences of their interaction. It was noted that it is necessary to form such a system that could respond to the numerous problems of the market economy, and state financial policy would cover all levels of the economy and would be integrally built on uniform methodological and organizational principles. The need to bring state financial control and audit of the use of state funds to international standards of state financial control has been proven, which will make it possible to improve the management of budget processes at all levels of budgets, interaction, and coordination of control bodies in the implementation of control measures and management decisions. A mechanism of state financial control and its structure has been developed, ensuring a high degree of preparation for conducting and implementing materials for control measures. It became evident that the methods of state financial control and their essence depend on the form of control considering the proposed mechanism. Measures to improve state financial control are proposed. The organizational structure of the unified system of state financial control is defined.
Keywords: financial control; financial and budgetary discipline; State Control and Audit Service; Concept of development of state internal financial control